2016
DOI: 10.1007/s00436-016-5029-y
|View full text |Cite
|
Sign up to set email alerts
|

Wide genetic variations at 18S ribosomal RNA locus of Cyclospora cayetanensis isolated from Egyptian patients using high resolution melting curve

Abstract: A variable clinical picture of cyclosporiasis including gastrointestinal tract (GIT) symptomatic or asymptomatic beside extraintestinal consequences suggests a possibility of heterogenicity of Cyclospora cayetanensis. The present work aimed to explore the possibility of genetic variation of C. cayetanensis using high-resolution melting (HRM) curve of polymerase chain reaction (PCR) amplified 18S rRNA genes. DNAs extracted from the stool samples of 70 cyclosporiasis patients were amplified and scanned by PCR/HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In this study, SSCP was performed differently as it involved a two-step nested PCR using the 18S rRNA gene, compared with those performed in other studies, and a minor genetic difference was identified among the strains obtained in 4 provinces in Turkey. In 2016, Hussein et al [22] reported that Cyclospora infections have a clinical picture that can change from being symptomatic to being asymptomatic. They claimed that the possible reason behind this variable clinical picture is the genetic heterogeneity of C. cayetanensis.…”
Section: Et Al Created a New Oligonucleotide Design With 116 Base Pairs Of Ccits2-f (5_-gcagtcacaggaggcatatatcc-3_) And Ccits2-r (5_-atgamentioning
confidence: 99%
“…In this study, SSCP was performed differently as it involved a two-step nested PCR using the 18S rRNA gene, compared with those performed in other studies, and a minor genetic difference was identified among the strains obtained in 4 provinces in Turkey. In 2016, Hussein et al [22] reported that Cyclospora infections have a clinical picture that can change from being symptomatic to being asymptomatic. They claimed that the possible reason behind this variable clinical picture is the genetic heterogeneity of C. cayetanensis.…”
Section: Et Al Created a New Oligonucleotide Design With 116 Base Pairs Of Ccits2-f (5_-gcagtcacaggaggcatatatcc-3_) And Ccits2-r (5_-atgamentioning
confidence: 99%